Effects of yoga breathing practice on heart rate variability in healthy adolescents: a randomized controlled trial - Maheshkumar Kuppusamy; Dilara Kamaldeen; Ravishankar Pitani; Julius Amaldas; Padmavathi Ramasamy; Poonguzhali Shanmugam; Venugopal Vijayakumar (Integrative Medicine Research)
Background: This study was conducted among healthy adolescents to assess the effects of a yoga breathing practice (Bhramari pranayama, Bhr.P) towards cardiac autonomic function using heart rate variability (HRV) parameters. Methods: Of the 730 eligible subjects screened, 520 healthy adolescents who met the inclusion and exclusion criteria were randomly assigned to either yoga breathing group (n = 260) or control group (n = 260). The yoga breathing group practiced Bhr.P. five days a week for a duration of six months while the control group continued with their daily routine without any intervention. Outcome measures were time and frequency domain of HRV in both groups which were assessed before and after the intervention using Lead II ECG. Linear models were used in the analysis of short term HRV. Results: After 6 months of yoga breathing, the time domain parameters of short term HRV showed significant (P < 0.05) improvement towards the parasympathetic domain. Frequency domain parameters also showed the same direction of changes. In contrast, control group subjects showed a trend towards a sympathetic domain. Conclusion: The present study showed a positive shift in cardiac autonomic modulation towards parasympathetic predominance after 6 months of yoga breathing practice among apparently healthy adolescents. Keywords: Yoga, Bhramari pranayama, Autonomic function, Heart rate variability, Adolescents